Chemical variations of sulfides and metal in enstatite chondrites—Introduction of a new classification scheme. (22nd December 2017) - Weyrauch, Mona; Horstmann, Marian; Bischoff, Addi
Abstract: In this study, the metal and sulfide compositions of 45 enstatite chondrites were analyzed to determine possible mineral‐chemical trends correlated with the petrologic type. Data for 35 additional samples were taken from the literature. Considering the data from this huge number of different E chondrite samples (80 in total), none of the trends previously described in the literature could be clearly confirmed. Also, among the opaque phases of enstatite chondrites, no other "new" correlations between mineral chemistry and the petrologic type were found. However, major differences in the sulfide and metal chemistry became obvious. Specifically, a certain number of chondrites in the EH and the EL groups have Cr in troilite above 2 wt%, Fe in niningerite or alabandite above 20 wt%, and lack abundant daubréelite. Differences were also found for Ni concentrations in kamacite. Thus, we propose a system for classifying E chondrites by defining four major subgroups: EHa, ELa, EHb, and ELb . All subgroups show full petrologic sequences that are similar to each other. This observation, in combination with the differences in sulfide and metal chemistry, suggests an origin of the samples from different parent bodies. Considering the anomalous E chondrite samples that neither fit in the previous classification scheme nor in the new one described here, the samples investigated in this study require at least eight different parent bodies.